ARCHAEOLOGICAL ANALYSIS OF THE ARCHITECTURE OF THE OLD MOSQUE IN ULEE KARENG - BANDA ACEH: ANALISIS ARKEOLOGI ARSITEKTUR MASJID TUHA IE MASEN ULEE KARENG - BANDA ACEH - Safrizal; Nasruddin AS (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
This study aims to analyze the architecture and its ornament of the old mosque in in Ulee Kareng – Banda Aceh. This old mosque is also known as the Masjid Tuha Ie Masen or Masjid Tuha Ulee Kareng. This study uses a qualitative approach through the descriptive analysis method. The research findings show that the shape of the Tuha Ie Masen Mosque building has undergone a change from its original form. There are several parts that have been renovated, including the roof, floors, and walls. The architectural form of the Tuha Ie Masen Ulee Kareng Mosque tends to be the same as that of old mosques in Indonesia. Archaeologically, the architectural form of the Tuha Ie Masen Mosque has similarities with the Tengku di Anjong Mosque and the Indrapuri Mosque. Meanwhile, when referring to the shape of mosque buildings outside Aceh, the Tuha Ie Masen Mosque also has similarities with mosques in the Java region, one of which is the Mosque of Demak. This can be seen from the shape of the roof, which has a terraced shape. As for the ornament, there are floral, geometric, and Islamic calligraphy motifs that are carved on several parts of the mosque.